Relationship Between Public Mental Health and Immune Status During the COVID-19 Pandemic: Cross-Sectional Data from Saudi Arabia - Alghamdi BS; Alatawi Y; Alshehri FS; Tayeb HO; Tarazi FI (Dove Medical Press, 2021)
Badrah S Alghamdi,1,2,* Yasser Alatawi,3,* Fahad S Alshehri,4 Haythum O Tayeb,5 Frank I Tarazi6 1Department of Physiology, Neuroscience Unit, Faculty of Medicine, King Abdulaziz University, Jeddah, Saudi Arabia; 2Pre-Clinical Research Unit, King Fahad Medical Research Center, King Abdulaziz University, Jeddah, Saudi Arabia; 3Department of Pharmacy Practice, Faculty of Pharmacy, University of Tabuk, Tabuk, Saudi Arabia; 4Department of Pharmacology and Toxicology, College of Pharmacy, Umm Al-Qura University, Makkah, Saudi Arabia; 5Division of Neurology, Department of Internal Medicine, Faculty of Medicine, King Abdulaziz University, Jeddah, Saudi Arabia; 6Department of Psychiatry and Neuroscience Program, Harvard Medical School and McLean Hospital, Boston, MA, USA*These authors contributed equally to this workCorrespondence: Badrah S Alghamdi Tel +966 567764144Email basalghamdi@kau.edu.saPurpose: Coronavirus disease 2019 (COVID-19) has evolved into a worldwide pandemic and continues to escalate exponentially in many countries across the globe. Recently, higher rates of psychological distress have been reported in several countries during the pandemic. Accordingly, the study aim was to investigate the relationship between public mental health and immune status during the COVID-19 pandemic.Methods: Participants of this cross-sectional study were 2252 national and foreign residents of Saudi Arabia. We used a web-based self-rated questionnaire to measure the association between psychological distress (Depression, Anxiety and Stress Scales [DASS-21]) and immune status (Immune Status Questionnaire [ISQ]) during the COVID-19 pandemic. We also investigated predictors of reduced immune status using binary logistic regression analyses.Results: Data from 1721 respondents showed that 17.5% of participants scored below the immune status cutoff (ISQ ˂ 6). Mean (± standard deviation) depression, anxiety, and stress scores in the reduced immune status group (ISQ ˂ 6) indicated moderate depression, anxiety, and stress (19.1 ± 11.4; 15.0 ± 9.6; 21.8 ± 11.2, respectively) and were significantly higher than scores in the normal immune status group (ISQ ≥ 6) (8.6 ± 9.1, P ˂ 0.0001; 5.0 ± 6.7, P ˂ 0.0001; 9.3 ± 9.3, P ˂ 0.0001, respectively). The regression analysis showed that age, anxiety, and stress were the only factors that significantly predicted the presence of reduced immune status.Conclusion: There is an association between mental health problems during the COVID-19 pandemic and immune response in the public, especially in elderly people.Keywords: mental health, COVID-19, immune status, Immune Status Questionnaire, psychological distress